2022
DOI: 10.1039/d2ta01929a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic modulation and surface reconstruction of cactus-like CoB2O4@FeOOH heterojunctions for synergistically triggering oxygen evolution reactions

Abstract: The cactus-like heterojunction with FeOOH nanosheets wrapped on CoB2O4 nanorod/nickel foam (CoB2O4@FeOOH/NF) was fabricated by hydrothermal and electrodeposition strategy for OER process. Benefiting from the cactus-like architecture for fast mass...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…All of these results support the successful construction of a NiFeP x /NiFeO x heterostructure with abundant amorphous–crystalline interfaces. Note that the coupled amorphous–crystalline interfaces may provide abundant active sites, induce the redistribution of electrons, and facilitate the adsorption and activation energy of intermediates, , thereby promoting the OER activity.…”
Section: Resultsmentioning
confidence: 99%
“…All of these results support the successful construction of a NiFeP x /NiFeO x heterostructure with abundant amorphous–crystalline interfaces. Note that the coupled amorphous–crystalline interfaces may provide abundant active sites, induce the redistribution of electrons, and facilitate the adsorption and activation energy of intermediates, , thereby promoting the OER activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the strong interactions between the two elements (Co and Fe) can effectively improve the electrocatalytic activity of alloys for OER [ 55 , 56 ]. The close contact between Mo 2 C and CoFe (heterojunction) should lead to the modification of the structure of CoFe alloy, contributing to the formation of highly active CoOOH/FeOOH [ 57 , 58 ]. Moreover, although the protecting role of NG can delay the oxidation of metallic species, the formation of ionic states (Co 2+ /Fe 2+ ) of Co/Fe is inevitable, which can effectively accelerate the formation of the key active species (CoOOH/FeOOH) for OER [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…29 In these heterostructures, the synthesis of FeOOH mostly relies on the hydrolysis of Fe 3+ under various conditions, for example, under hydrothermal or electrodeposition conditions. [30][31][32] However, the construction of elegant nanostructures under relatively mild reaction conditions remains a challenge. 33,34 Recently, as exampled by Ping Xu and co-workers, the property of Fe salts that are used as raw materials may influence the crystalline phase and morphology of FeOOH greatly.…”
Section: Introductionmentioning
confidence: 99%